A framework for accelerated product innovation in a big data environment - Zhan, Yuanzhu (2017)
This dissertation is concerned with the best approaches for accelerated product innovation in a big data environment. It describes the development and examining of a framework consisting of three sets of different phases to support managers to attain accelerated product innovation in high-tech industries. This research also investigates the roles of big data in facilitating new product development, and the factors for successful implementation of big data.